A clinical rule (sex, contralateral occlusion, age, and restenosis) to select patients for stenting versus carotid endarterectomy - Touzé, Emmanuel; Trinquart, Ludovic; Felgueiras, Rui; Rerkasem, Kittipan; Bonati, Leo H.; Meliksetyan, Gayané; Ringleb, Peter A.; Mas, Jean-Louis; Brown, Martin M.; Rothwell, Peter M. (Stroke, 2013)
Background and Purpose: Compared with carotid endarterectomy (CEA), carotid angioplasty and stenting (CAS) is associated with a higher risk of procedural stroke or death especially in patients with symptomatic stenosis. However, after the perioperative period, risk is similar with both treatments, suggesting that CAS could be an acceptable option in selected patients. - Methods: We performed systematic reviews of observational studies of procedural risks of CEA or CAS and extracted data on 9 predefined risk factors (age, contralateral carotid occlusion, coronary artery disease, diabetes mellitus, sex, hypertension, peripheral artery disease, and type and side of stenosis). We calculated pooled relative risks of procedural stroke or death. Factors with differential effects on risk of CAS versus CEA were identified by interaction tests and used to derive a rule. The rule was tested using individual patient data from randomized trials of CAS versus CEA from the Carotid Stenting Trialists’ Collaboration (CSTC). - Results: We identified 170 studies. The effects of sex, contralateral occlusion, age, and restenosis (SCAR) on the procedural risk of stroke or death differed. Patients with contralateral occlusion or restenosis and women <75 years were at relatively low risk for CAS (SCAR negative), with all others being high risk (SCAR positive). Among the 3049 patients in the CSTC validation, 694 (23%) patients were SCAR negative. The pooled RR of procedural stroke and death with CAS versus CEA was 0.93 (0.49-1.77; P=0.83) in SCAR-negative and 2.41 (1.68-3.45; P<0.0001) in SCAR-positive patients (P [interaction]=0.05). - Conclusions: The SCAR rule is potentially useful to identify patients in whom CAS has a similar risk of perioperative stroke or death to CEA.
Gesehen am 10.02.2022